Assessing Novel Lidar Modalities for Maximizing Coverage of a Spaceborne System through the Use of Diode Lasers - Johannes N. Hansen; Steven Hancock; Ludwig Prade; Gerald M. Bonner; Haochang Chen; Ian Davenport; Brynmor E. Jones; Matthew Purslow (Remote Sensing, 2022)
Current satellite lidars have sparse spatial coverage, leading to uncertainty from sampling. This complicates robust change detection and does not allow applications that require continuous coverage. One potential way to increase lidar sampling density is to use more efficient lasers. All current spaceborne lidars use solid-state lasers with a limited efficiency of 5–8%. In this paper, we investigate the potential for using diode lasers, with their higher efficiencies, as an alternative. Diode lasers have reported efficiencies of about 25% and are much smaller and lighter than solid-state lasers. However, they can only emit good beam quality at lower peak powers, which has so far prevented them from being used in spaceborne lidar applications. In this paper, we assess whether the novel lidar modalities necessitated by these lower peak powers are suitable for satellite lidar, determined by whether they can match the design performance of GEDI by being able to accurately measure ground elevation through 98% canopy cover, referred to as having “98% beam sensitivity”. Through this, we show that a diode laser can be operated in pulse train or pulse compressed lidar (PCL) mode from space, using a photon-counting detector. In the best case scenario, this setup requires a detected energy of <semantics>Edet=0.027 fJ</semantics> to achieve a beam sensitivity of 98%, which is less than the 0.28 <semantics>fJ</semantics> required by a full-waveform solid-state lidar instrument, exemplified by GEDI. When also accounting for the higher laser and detector efficiency, the diode laser in pulse train mode requires similar shot energy as a photon counting solid-state laser such as ICESat-2 which along with the higher laser efficiency could result in a doubling of coverage. We conclude that there is a clear opportunity for diode lasers to be used in spaceborne lidars, potentially allowing wider coverage through their higher efficiencies.